Development of thematic e-modules oriented on the ability to write descriptions of students in class V of SDN Boto, Tuban district - Wiratama, Novialita Angga (Universitas Nusantara PGRI Kediri, 2023)
Based on the observation results of descriptive writing skills in class V students and interviews with teachers of SDN Boto, Semanding District, Tuban Regency, students' writing ability was low. Students have difficulty determining the topic of writing so that students do not want to start writing activities. In learning activities, students are only given assignments from LKS so that in writing descriptive essays students are not able to involve their five senses to put their ideas into writing. Preliminary data from analysis of student scores obtained data on the number of students in grade 5 were 25 students, only 5 students were able to complete writing the descriptive essay. So that only 20% of classical percentages have the ability to write descriptions. Based on this background, thematic e-modules were developed to make it easier for students to write descriptions of class V students at Boto 5 Elementary School. This type of research was R&D with four stages. The purpose of this e-module development research is to determine feasibility level of linguists, materials, and media. The results of validation by design experts show that the quality of learning e-module is in stage 1 assessment component with an achievement level of 82.85% with a